Expenditure patterns and welfare effects of inflation - estimates of a true cost-of-living index - Irvine, Ian; McCarthy, Colm (Economic & Social Studies, 1978)
Inflation can have two principal kinds of redistributive effects. Even when relative prices are constant, the position of creditors worsens vis-a-vis that of debtors, unless the inflation is perfectly anticipated. If relative prices change as well, consumers of the goods whose relative prices have risen are also at a disadvantage. Inflation need not be accompanied by relative price movements, which in turn can occur when the overall price level is stable. Changes in relative prices have, however, been a noticeable feature of the recent inflation and in this paper an attempt is made to quantify their redistributive consequences. The theoretical tool employed is the `true? cost-of-living index, by no means a new idea in demand analysis but one which is not often utilised and which has never, to our knowledge, been used with Irish data. The second section of the paper discusses true cost-of-living indices and their estimation. The third section contains the empirical results and is followed by a discussion and conclusions. Data, sources and methods are treated in the appendix.
Keywords: Inflation - Ireland; Cost of living indices